Design and Validation of a Contextual Project-Based Organic Chemistry Practicum Module for Undergraduate Learning - Pino Ramadani; Maasje Catherine Watulingas; Farah Erika; Agung Rahmadani; Fitriah Khoirunnisa (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to design and validate a project-based organic chemistry practicum module that integrates a contextual approach, which is designed to facilitate students’ conceptual understanding, practical skills, engagement, learning motivation, and overall learning experience during laboratory practicum activities. Methodology: This study employed the Research and Development (R&D) method utilizing the ADDIE model specifically for the Analysis, Design, and Development stages. It represents early development phase focused on design and expert validation. Data were collected through interviews and questionnaires. Module validation carried out by subject matter and media validators using Likert scale instruments and Gregory matrix calculations to ensure validity. Main Findings: This study’s project-based, contextually integrated organic chemistry practicum module operationalizes PjBL through structured stages. Contextual learning integrates authentic phenomena with real-world applications. Validation involved two subject matter and two media validators, yielding Gregory coefficients of 1.00 for both. The module is highly valid, and future studies should test its effectiveness and practicality in enhancing conceptual understanding or 21st-century 4C skills. Novelty/Originality of this study: This study developed an organic chemistry practicum module that systematically integrates contextual phenomena across all PjBL phases. Unlike previous PjBL modules lacking contextual integration or conventional recipe-style modules with limited learning impact. This module addresses gaps in conceptual reasoning, contextual relevance, and competency, while reducing procedural learning and enhancing conceptual understanding, practical skills, 21st-century skills, and integrated science learning.